Development of apigenin loaded gastroretentive microsponge for the targeting of Helicobacter pylori - Mohammed Jafar; Mohd Sajjad Ahmad Khan; Mohammed Salahuddin; Saira Zahoor; Hanan MohammedHesham Slais; Layali Ibrahim Alalwan; Heba Radhi Alshaban (Elsevier, 2023)
The goal of the present work was to invent an apigenin-stacked gastroretentive microsponge to target H. pylori. The quasi-emulsion technique was used to prepare microsponges, which were then tested for various physicochemical properties, in-vivo gastric retention, and in-vitro anti-H. pylori study. The microsponge that demonstrated a comparatively good product yield (76.23 ± 0.84), excellent entrapment efficiency (97.84 ± 0.85), sustained in-vitro gastric retention period, and prolonged drug release were chosen for further investigations. The microsponge's SEM analysis showed that it had a spherical form, porous surface, and interconnected spaces. No drug-polymer interactions were detected in the FTIR investigation. Apigenin was found to be dispersed in the microsponge's polymeric matrix according to DSC & XRD investigations. Moreover, the microsponge in the rat's stomach floated for 4 h, according to the ultrasonography. The antibacterial activity of apigenin against H. pylori was nearly two folds more than the pure apigenin and had a more sustained release in the best microsponge, according to the in vitro MIC data, when compared to pure apigenin. To sum up, the developed gastroretentive microsponge with apigenin offers a viable alternative for the efficient targeting of H. pylori. But more preclinical & clinical studies of our best microsponge would yield considerably more fruitful results.